How to talk so little kid will listen : a survival guide to life with children ages 2-7 - Faber, Joanna; King, Julie (London : Piccadilly, 2017)
Discover tried and tested communication strategies to survive - and thrive - with kids ages 2-7 The all-new content in this book deals with struggles familiar to every parent, relative, teacher and childminder. How do you respond to the toddler who won't brush his teeth? The preschooler who pinches the baby? The child who throws everything she can reach? It's hard to be a little kid. It's hard to be an adult responsible for that little kid. And it's really hard to think about effective communication when the toast is burning, the baby is crying and you're exhausted. This book will help readers do just that. Organized according to everyday challenges and conflicts, and including real-life examples and the series' trademark cartoons, this book is a survival manual of communication tools, including a chapter that addresses the special needs of children with sensory processing or autism spectrum disorders.
Includes index.
Keywords: Parenting; Interpersonal communication; Interpersonal communication in children